Moderate Wine and Alcohol Consumption: Beneficial Effects on Cardiovascular Disease - Booyse, Francois M.; Parks, Dale A. (Thrombosis and Haemostasis, 2001)
Cardiovascular disease, in particular coronary heart disease (CHD) and associated myocardial infarction (MI), is the leading cause of death among adults in the Western world (1). Although CHD is a complex multi-factorial disease, major insights have been gained in our understanding of the etiology underlying the initiation and progression of CHD. The pathogenesis of CHD and the ensuing atherothrombotic complications resulting in MI, involves the complex and often synergistic interplay between multiple dysfunctional cellular and molecular mechanisms that have been altered through interactions with various environmental and/or systemic factors (i. e. CHD risk factors). Typically, these deleterious effects are exerted at the level of the heart muscle, blood vessels and blood components and result in dysfunction in endothelial cells (ECs), smooth muscle cells, cardiac myocytes, blood cells (platelets and monocytes) and plasma components (lipoproteins, fibrinogen, clotting factors, etc.). These combined effects will then contribute further to the initiation and progression of CHD and eventual MI. Consequently, any systemic factors (such as alcohol or wine components) that will reduce, minimize or inhibit these induced dysfunctions will be expected to reduce the overall risk for cardiovascular disease and CHD-related mortality.
Keywords: Alcohol; polyphenols; endothelial cells; platelets; CHD